Epilepsy and outcome in FOXG1‐related disorders. Issue 8 (16th May 2014) - Seltzer, Laurie E.; Ma, Mandy; Ahmed, Sohnee; Bertrand, Mary; Dobyns, William B.; Wheless, James; Paciorkowski, Alex R.
Summary Objective FOXG1‐related disorders are associated with severe intellectual disability, absent speech with autistic features, and epilepsy. Children with deletions or intragenic mutations of FOXG1 also have postnatal microcephaly, morphologic abnormalities of the corpus callosum, and choreiform movements. Duplications of 14q12 often present with infantile spasms, and have subsequent intellectual disability with autistic features. Long‐term epilepsy outcome and response to treatment have not been studied systematically in a well‐described cohort of subjects with FOXG1‐related disorders. We report on the epilepsy features and developmental outcome of 23 new subjects with deletions or intragenic mutations of FOXG1, and 7 subjects with duplications. Methods Subjects had either chromosomal microarray or FOXG1 gene sequencing performed as part of routine clinical care. Development and epilepsy follow‐up data were collected from medical records from treating neurologists and through telephone parental interviews using standardized questionnaires. Results Epilepsy was diagnosed in 87% of the subjects with FOXG1‐related disorders. The mean age of epilepsy diagnosis in FOXG1 duplications was significantly younger than those with deletions/intragenic mutations (p = 0.0002). All of the duplication FOXG1 children with infantile spasms responded to hormonal therapy, and only one required long‐term antiepileptic therapy. In contrast, more children with deletions/intragenic mutations required antiepileptic drugs on follow‐up (p < 0.0005). All subjects with FOXG1‐related disorders had neurodevelopmental disabilities after 3 years of age, regardless of the epilepsy type or intractability of seizures. All had impaired verbal language and social contact, and three duplication subjects were formally diagnosed with autism. Subjects with deletion/intragenic mutations, however, had significantly worse ambulation (p = 0.04) and functional hand use (p < 0.0005). Significance Epilepsy and developmental outcome characteristics allow clinicians to distinguish among the FOXG1‐related disorders. Further genotype–phenotype studies of FOXG1 may help to elucidate why children develop different forms of developmental epilepsy. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here